A new insight into oxidation mechanisms of sulphide minerals - Alireza Javadi Nooshabadi; Kota Hanumantha Rao (International Mineral Processing Congress, 2014)
Formation of hydrogen peroxide (H2O2), an oxidizing agent stronger than oxygen, by sulphide minerals during grinding was examined. It was found that pyrite (FeS2), chalcopyrite (CuFeS2), sphalerite ((Zn, Fe) S), and galena (PbS) generated H2O2 in pulp liquid during wet grinding and also when the freshly ground solids are placed in water immediately after dry grinding. Pyrite produced more H2O2 than other minerals and the order of H2O2 production by the minerals was found to be pyrite > chalcopyrite > sphalerite > galena. The pH of the water influenced the extent of hydrogen peroxide formation with greater amounts of H2O2 produced at highly acidic pH. Furthermore, the effect of mixed sulphide minerals, i.e., pyrite-chalcopyrite, pyrite-galena, chalcopyrite-galena and sphalerite-pyrite, sphalerite-chalcopyrite and sphalerite-galena on the formation of H2O2 showed increasing H2O2 formation with increasing pyrite fraction. There is clear correlation of the amount of H2O2 production with the rest potential of the sulphide minerals; the greater the rest potential of a mineral the greater the formation of H2O2. This study highlights the necessity of revisiting the electrochemical and/or galvanic interactions between sulphide minerals, and interaction mechanisms between pyrite and other sulphide minerals in terms of their flotation behavior in the context of inevitable H2O2 existence in the pulp liquid.